Participatory development of scaling plan as a part of low emission roadmap in rice production of Mekong River Delta - Bui, Tan Yen; Sander, Björn Ole; Nelson, Katherine; Vu, Duong Quynh (2020)
This paper presents an engagement study that focuses on a provincial low emission roadmap in rice production. Results obtained in the study of An Giang province show that AWD adoption is strongly influenced by biophysical conditions and technical guidance, while adoption of environmentally friendly straw management is mainly driven by market, rainfall distribution and quality of transportation network. In An Giang’s districts, adoption of LET can be improved in the next 5-year plan. The implementation targets and required collective actions are in relation to improvement of infrastructure, policy and communication, and vary from district to district. With engagement of local stakeholders, this workshop has identified challenges for the implementation of LET and highlighted the locally proposed solutions as the way to overcome current constraints and connect the last mile from research to field implementation. This paper provides insights of LET adoption and implementation potential in An Giang, which also have implications for LET scaling in other provinces in the Mekong River Delta.